Impact of Marketing Expenditure on Sales and Profitability of Listed Manufacturing Companies in Nepal - Agrahari, Khusboo; Karki, Dipendra; Rai, Ram Bahadur (Koshi Pravah: Multidisciplinary Peer Reviewed Journal, 2023)
Marketing expenses are important corporate operations that have an impact on lead generation and revenue in an organization. In today’s business environment, it is essential to know how marketing expenditures affect a company’s performance. Based on this viewpoint, the primary goal of this study was to determine whether marketing expenditures had an impact on companies’ performance. The study examined the impact of marketing expenditures on sales and profitability of listed manufacturing companies in Nepal. This study is based on secondary data collected from six listed manufacturing companies for six years, from 2016/17 to 2021/22. A descriptive statistic, correlation analysis, and simple linear and non-linear regression methods were applied to analyze the data. The study concludes that there was a non-linear relationship of marketing expenditure with sales and profitability. It indicates that there was a certain level of marketing expenditure that maximizes sales and profitability. The company needs to analyze what amount of money, time, and effort are put into marketing expenditures. Companies face the danger of inducing a price orientation in the market if they employ promotions excessively. A balanced marketing budget is crucial to the company's prosperity. With this view, the marketing manager should provide an accurate annual marketing budget that maximizes sales and profitability for the company.